A novel method of selectively enriching and separating rare earth elements from rare-earth concentrate under super gravity. (15th March 2019) - Lan, Xi; Gao, Jintao; Du, Yu; Guo, Zhancheng
Graphical abstract: Highlights: A novel method was proposed to extract REEs from rare-earth concentrate. REEs were selectively enriched to single rare earth oxide fluoride at 1473–1773 K. Selective separation of rare earth oxide fluoride was conducted in super gravity. High-purity Re-rich phase with high ReO content was attained and characterized. Abstract: The Bayan Obo rare-earth concentrate was obtained through mineral processing and massively disposed at the tailing dams. For efficient extraction of the rare earth elements (REEs) from the rare-earth concentrate, a novel approach was proposed to selectively enrich and separate REEs as rare earth oxide fluoride ([Ce, La, Pr, Nd]OF) phase under super gravity. Firstly, the mineral reconstruction behavior of the rare-earth concentrate revealed that REEs were selectively enriched into the rare earth oxide fluoride phase with the temperature's rising to 1473 K–1773 K under a reductive atmosphere. Subsequently, selective separation of the rare earth oxide fluoride phase was conducted under super gravity at the enriching temperature range, where the REEs were enriched as the single Re-rich phase while other minerals formed the molten slag. Accordingly, high-purity rare earth oxide fluoride phase with a high ∑ReO content of 90.35 wt.% was efficiently separated from the rare-earth concentrate under super gravity at 1773 K with G = 1000 for 10 min, which was accurately characterized for the first time to supplement some lacking data for the Re-rich phase. In addition, this manuscript provided a novel physical separation method for mineral processing.